Analysis of Basic Brake Discs Power Distribution of EMUs - 战成一; 韩龙; 宋德刚 (机车电传动)
Process of basic brake power setting of EMUs was introduced. With instances, mode and means of basic brake discs power distribution were analyzed emphatically, which were validated reasonable by simulation results.